STRATEGI MALAYSIA DALAM MENINGKATKAN WISATAWAN INDONESIA MELALUI SLOGAN “MALAYSIA TRULY ASIA” SEBAGAI NATIONAL BRANDING PADA TAHUN 2013 - 2014 - Putri, Adina Tria; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study discusses how a slogan to become National Branding can affect the number of foreign tourists, especially those implemented by the State of Malaysia, namely "Malaysia, Truly Asia". Since it was first formed in 1999, this slogan has been able to bring significant tourists. The number of foreign tourists is increasing every year, so it succeeded in bringing in more than 7.4 million tourists and helping the country's economy during the economic crisis in 2008. "Malaysia, Truly Asia" achieved success in 2014, as well as making the year with the number of tourists most in the State of Malaysia. Keywords: Malaysia, Truly Asia, Tourists, Overseas, National, Branding, Malaysia.